Impact of hydroxyurea on clinical and biological parameters of sickle cell anemia in children in Abidjan - MIREILLE YAYO- AYE; Adia Eusèbe Adjambri; Boidy Kouakou; Rebecca N'guessan-Blao; Louis Missa Adjé; Taïratou Kamagaté; Vincent Yapo; Duni Sawadogo (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The lives of individuals affected by sickle cell disease are marked by painful crises sometimes accompanied by complications. Curative treatments such as bone marrow transplantation or gene therapy exist, but are not currently performed in Côte d'Ivoire. Treatment with hydroxyurea remains an effective alternative. The aim of our study is to contribute to improving the management of children with sickle cell disease.